On the whereabouts of CSP-CASL – A survey - Gimblett, Andy; Kahsai, Temesghen; O'Reilly, Liam; Roggenbach, Markus (Electronic Communications of the EASST, 2013)
CSP-CASL is but one of the many languages for which Bernd Krieg-Brueckner (BKB) had a great deal of influence throughout its development process: from the initial idea of working towards an integration of the process algebra CSP with the algebraic specification language CASL, to the design of the concrete syntax, and also to tool support for CSP-CASL, where the theorem prover Isabelle should provide the common platform. In all this, BKB provided inspiration and guidance, funding, and also a helping hand when needed. This paper provides a survey on the technology developed so far for CSP-CASL, covering results of a theoretical nature, an industrial case study, theorem proving support as well as a testing approach. In honour of BKB’s 60th birthday, this survey documents what has become out of one of BKB’s visions.